Socio-demographic determinants of fast-food consumption in Malaysian young adults - Nurhanim Mohd Hatta,; Asma’ Ali,; Aziz Yusof,; Wan Hafiz Wan Zainal Shukri,; Khairil Shazmin Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Fast-food is the fastest-growing food category in the world, offering young adults a quick, affordable, and readily available alternative to home-cooked meals. The objective of this study was to determine the socio-demographic determinants of the most frequent fast-food consumption among young adults in Malaysia. This cross-sectional study involved 405 Malaysian young adults aged 18 to 29 who participated in an online survey. This self-administered online questionnaire of habitual fast-food consumption was evaluated using a modified Fast-food Frequency Questionnaire comprised of 30 food items, while the socio-demographic profile was determined by age, gender, ethnicity, monthly household income, marital status, residence, and educational level. IBM SPSS Statistics version 25 (SPSS IBM, New York, USA) was used to analyse the data. The results indicated that the most frequently consumed fast-foods were fried chicken (77.6% of habitual consumption), ice cream (41.3%), and burgers (40%). A chi-square independence test revealed a statistically significant association between urban and rural residence and high fast-food consumption (i.e., fried chicken): c2(2, N = 405) = 22.924, p = 0.001. However, there is no association between consumption of fast-food and gender (c2(2, N = 405) = 0.044, p = 0.834), fast-food and age (p = 0.403), or fast-food and educational level (p > 0.05). Taken together, these findings have provided more information on the habitual consumption of fast-food by young adults. The Malaysian government and other health authorities may be able to develop an action plan to reduce obesity rates and other diseases associated with fast-food consumption among young adults.